Formulation of Policy on The Implementation of Criminal Punishment Sanctions and Rehabilitation Against Children as Drug Abuse Perpetrators - Ridwan, Ridwan; Witjaksana, Budi; Purnama, Jaka (Pusat Publikasi Nusantara, 2025)
This research aims to analyze the cost estimation of risk mitigation in the construction project of the Pamekasan Regency Regional General Hospital. Construction projects are highly complex and often face multiple risks, including technical, environmental, and management factors, which can significantly affect cost efficiency and project completion time. Failure to address these risks appropriately can lead to budget overruns, prolonged delays, and compromised construction quality. The research employs a quantitative approach using the Probability and Impact Matrix and Severity Index to systematically identify, categorize, and assess the impact of construction risks. The findings reveal that the total estimated cost of risk mitigation reaches Rp. 290,450,000, which primarily covers additional labor, high-quality material procurement, and the application of technology for project monitoring. To mitigate these risks, several key strategies have been implemented, including stricter contract management, improved stakeholder communication, enhanced workforce capacity, and advanced project monitoring techniques. Furthermore, digital-based monitoring systems and early risk detection mechanisms are suggested to prevent major disruptions in the project workflow. By implementing effective mitigation strategies, the project is expected to operate more efficiently, minimize unnecessary costs, and adhere to the planned construction schedule. The study highlights the importance of proactive risk management in large-scale infrastructure projects, providing valuable insights for contractors, project managers, and policymakers involved in hospital construction. These findings emphasize the need for continuous evaluation and adaptation of risk mitigation strategies to ensure successful project execution.